Desain Rekayasa dan Analisis Struktur Tabung Plastic Melter Menggunakan Simulasi FEA (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Plastic waste has become one of the main environmental problems due to its nature, which is difficult to decompose naturally and can cause environmental pollution. One alternative waste treatment method that can be applied is to use a plastic melter to melt and recycle plastic waste into useful products. However, the design of plastic melters often lacks consideration of structural strength and safety aspects during the operation process. This study aims to design and engineer a plastic melter using the Finite Element Analysis (FEA) simulation approach to analyze structural resistance to thermal and mechanical loads that occur during the operation process. The research method was carried out through 3D design modeling of plastic melter components using Solidworks software, followed by analysis with FEA simulation on the main component, namely the melting tube. The parameters analyzed include the distribution of von Mises stress, the amount of displacement, and the safety factor. The analysis results show that the analyzed components experience von Mises stress distribution and displacement that are still below the material tolerance limits, with safety factor values above the recommended safety limits. Thus, the resulting plastic melter design is declared safe and can proceed to the manufacturing process. Therefore, the plastic melter design is safe, strong, and feasible to be realized as an effective and sustainable plastic waste processing technology solution.